2021
DOI: 10.1016/j.psychres.2021.113959
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Related Symptoms of Anxiety, Depression, and PTSD among US Adults

Abstract: During the COVID-19 pandemic, social distancing measures often resulted in individual isolation, which can lead to adverse mental outcomes. We collected online questionnaires from 3,952 US adults to examine the impact of “shelter-in-place” guidelines on mental health, and to explore potential disparities and modifiable factors. Self-reported anxiety, depression, and PTSD symptoms were associated with more restrictive quarantine. Younger adults, women, those with lower income, more insecurity, more media exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 22 publications
3
32
0
1
Order By: Relevance
“…Reports on the pandemic in the empirical literature began emerging in early 2020. We expect that this body of work will continue to expand exponentially from the approximately 3000 articles available as of this writing (Feingold et al, 2021;Jiang et al, 2020;Maalouf et al, 2021;Zhu et al, 2021). Critically, there has been a renewed call to expand the definition of a qualifying Criterion A trauma and consider the pandemic, in general, to be a Criterion A stressor (Wathelet et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the pandemic in the empirical literature began emerging in early 2020. We expect that this body of work will continue to expand exponentially from the approximately 3000 articles available as of this writing (Feingold et al, 2021;Jiang et al, 2020;Maalouf et al, 2021;Zhu et al, 2021). Critically, there has been a renewed call to expand the definition of a qualifying Criterion A trauma and consider the pandemic, in general, to be a Criterion A stressor (Wathelet et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Socially isolated young people, condemned to constant contact with the internet, find themselves in sorrowful situations where the satisfaction of their basic needs (the need for natural, unrestrained social contacts) was impossible. This situation evokes fear and insecurity, which leads to a range of heightened reactions such as stress, post-traumatic stress disorder (PTSD), anxiety, depression, behavioral changes, sleep problems, eating disorders, alcohol and drug abuse [8][9][10][11][12][13]. It would seem that feelings of stress and fear are similarly distributed throughout the population.…”
Section: Introductionmentioning
confidence: 99%
“…Poor socio-economic conditions have also affected mental health during COVID-19 [7][8][9]. Studies from the USA as well as other countries reported that females, younger age groups, and people with unsteady income perceived higher stress during the pandemic [8][9][10]. COVID-19 outcomes in the United States reflected racial disparities; African-American participants and Hispanic participants were reported to have several-fold higher risks of hospitalization and death due to COVID-19 than White participants [11].…”
Section: Introductionmentioning
confidence: 99%